Adolescences - Ingrassia, Massimo; Benedetto, Loredana (IntechOpen, 2022)
The studies in this book focus on factors that challenge the developmental paths of adolescents. The themes are: online experience (i.e., the overuse of screens, the proliferation of inappropriate videos, or parental pressures for children to remain always connected), the difficulties of pandemic times (i.e., coping with anxiety or illness), and two conditions of great fragility (that of being a migrant refugee minor, or an adolescent with severe mental disorder). These topics illustrate the multiple adolescent development pathways that inspire the plural title of the volume: Adolescences. Each author suggests protective factors (personal, family, educational, and friendship-related) that can contribute to promoting a healthy developmental outcome.